Using shock control bumps to improve engine intake performance and operability. (December 2020) - John, A.; Bower, J.; Qin, N.; Shahpar, S.; Smith, A.
Abstract: Shock control bumps can be used to control and weaken the shock waves that form on engine intakes at high angles of attack. In this paper, it is demonstrated how shock control bumps applied to an engine intake can reduce or eliminate shock-induced separation at high incidence, and also increase the incidence at which critical separation occurs. Three-dimensional Reynolds-average Navier–Stokes (RANS) simulations are used to model the flow through a large civil aircraft engine intake at high incidence. The variation in shock strength and separation with incidence is first studied, along with the flow distribution around the nacelle. An optimisation process is then employed to design shock control bumps that reduce shock strength and separation at a fixed high incidence condition. The bump geometry is allowed to vary in shape, size, streamwise position and circumferential direction around the nacelle. This is shown to be key to the success of the shock control geometry. A further step is then taken, using the optimisation methodology to design bumps that can increase the incidence at which critical separation occurs. It is shown that, by using this approach, the operating range of the engine intake can be increased by at least three degrees.